Effect of Sampling Time and Sampling Media During Filter and Liquid Impingement-Based Sampling on Collected Bacterial Viability, Culturability, and DNA Concentrations - Shu-An Lee; Yee-Lynn Low; Atin Adhikari; Wei-Kuang Wang; Chih-Ming Liang; Li-Te Chang; Chuen-Jinn Tsai (Aerosol and Air Quality Research)
Abstract Background Airborne pathogenic bacteria sampling is critical for microbial risk assessment. The stress induced by sampling methods such as filtration and liquid impingement can affect the bioactivity and integrity of collected microbial samples, but the roles of sampling time, media, and replenishment strategies remain unclear. Methods This study evaluated the culturability, viability, and DNA loss percentage (DLP) of collected Escherichia coli using two common sampling techniques: filter-based sampling (Button Sampler) with two filter types (mixed cellulose ester (MCE) and polycarbonate (PC)) and liquid impingement-based sampling (BioSampler) with three collection media (DI water, PBS, and a Tween mixture (TM)). Sampling times ranged from 0 to 120 minutes. Replenishment effects were assessed for liquid impingement-based sampling. Results Longer sampling times significantly reduced bacterial culturability and viability across all methods. MCE filters showed better performance than PC filters, with lower DLP. TM as the impingement medium with replenishment preserved the highest viability (89.91%) and culturability (69.64%) at 120 min, with the lowest reaerosolization loss (0.12%) and DLP (36.27%). DLP was negatively correlated with viability (r = –0.762, p 0.01) and culturability (r = – 0.638, p 0.01). Conclusions Sampling media, replenishment, and time substantially affect the bioactivity and DLP of collected microbial sample. TM-based BioSampler with replenishment is preferable for environmentally sensitive bacteria. Sampling time should be minimized to reduce DNA loss and ensure microbial viability and culturability. Graphical abstract